Investigation on Eco-Friendly Natural Dyes: Chemistry, Dyeing and Antimicrobial Properties of Helichrysum bracteatum - Sivakumar, R.; Jayaprakasam, R.; Renuga, V.; Sasikumar, C. (Asian Journal of Chemistry, 2010)
The present textile processing methods causes enormous damage to environment by the way of water pollution by releasing toxic chemicals, non-biodegradable dyes, total dissolved solids and sludge from effluent treatment plants. Thus the need of the hour is to find eco-friendly methods of dyeing. One such possibility of eco-friendly dyeing is to screen natural resources for the industrial dyeing application. The present work involves to investigate a new plant sources for dyeing textile materials. Accordingly the Helichrysum bracteatum herb with golden yellow flowers was investigated. It was found to contain major two flavonoids namely 6,3',4',5'-tetrahydroxy-4-O-b-D-glucopyranosylaurone (bractein) and 6,3',4'-trihydroxy-4-O-b-D- glucopyranosylaurone (cernuoside). Further on dyeing with natural and metallic mordants various intensities of colour shades for fabrics with acceptable fastness properties was obtained. It is worthy to note that no toxic chemicals were utilized in the entire process. On testing for antimicrobial activity, samples showed remarkable bacterial activity in assay conditions on Escherichia coli, Proteus vulgaris and Salmonella typhi. With increasing concentrations of dye, the zone of inhibition is increasing almost linearly.